DeLone–McLean Information System Success Model Revisited: The Separation of Intention to Use-Use and the Integration of Technology Acceptance Models - Mardiana, Siti; Tjakraatmadja, Jann H.; Aprianingsih, Atik (International Journal of Economics and Financial Issues, 2015)
DeLone–Mclean model is an established and well-known information system (IS) model for assessing IS success. Based on some meta-analysis studies of DeLone–Mclean model, it is revealed that some relationships in the construct are not significant. As such, the construct validity is questionable and might lower the predicting power. A thorough literature review had been done to break down the underlying theoretical concept of DeLone–McLean model. Based on the literature review, several solutions are proposed including the separation between intention to use and use and the integration of technology acceptance models (TAMs) and unified theory of acceptance and use of technology (UTAUT). The integration of TAM and UTAUT into DeLone–McLean model is needed to provide proper antecedents for intention to use since TAMs has a stronger and sound theoretical background for predicting behavioral intention (BI). Further exploration into TAM and UTAUT literature has revealed that only perceived usefulness (PU), performance expectancy (PE), effort expectancy (EE), and social influence (SI) that significantly predict BI (intention to use). Based on these findings, PU, PE, EF and SI are integrated into DeLone–McLean model as the additional antecedents for intention to use. Keywords: Information System Success; Delone–Mclean IS Model; Technology Acceptance Models; Unified Theory of Acceptance and Use of Technology JEL Classifications: M00